Aquachlorido{2-[2-(cyclohexylcarbamothioyl-kappa S)hydrazinylidene-kappa N-1]propanoato(2-)}phenyltin(IV) - Abu Affan, M.; Salam, M.A.; Jusoh, I.; Ng, S.W.; Tiekink, E.R.T. (International Union of Crystallography, 2010)
In the title organotin compound, [Sn(C6H5)(C10H15N3O2S) Cl(H2O)], the Sn atom is coordinated by the S, O, and imine N atoms of the dinegative tridentate ligand, a chloride ligand, the ipso-C atom of a phenyl ligand and by a water molecule in a distorted octahedral coordination environment. Coordinated water molecules link the organotin molecules by forming O-H center dot center dot center dot O hydrogen bonds with both carbonyl and carboxylate O atoms, leading to 12-membered {center dot center dot center dot OCO center dot center dot center dot HOH center dot center dot center dot}(2) synthons. This results in the formation of supramolecular chains along the c axis. The chains pack in the ac plane and stack along the b axis with links between layers afforded by N-H center dot center dot center dot Cl hydrogen bonds.